Antibacterial Potential of Sauropus androgynus (L.) Merr Methanolic Extract Against Escherichia coli and Pseudomonas aeruginosa - Maharani Ajeng Astiti; Syarah Ardha Fauzia; Bintang Arnazora Putri (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2026)
Background: Contamination of food by pathogenic bacteria such as Escherichia coli and Pseudomonas aeruginosa causes significant food poisoning globally. The use of natural preservatives serves as an alternative to synthetic preservatives. Phytochemical compounds with antibacterial activity hold great potential for the development of natural food preservatives. Purpose: This study aimed to identify the phytochemical constituents and evaluate the antibacterial potential of fresh Katuk (Sauropus androgynus (L.) Merr) leaf methanolic extract against both bacteria. Method: The extract was obtained via maceration, followed by phytochemical screening and antibacterial activity assays using the agar well diffusion method at extract concentrations of 20%, 40%, 60%, and 80% (w/w), with chloramphenicol 0.1% as the positive control and distilled water as the negative control. Data were statistically analyzed using One-Way ANOVA followed by Tukey's Post-hoc HSD test (p = 0.05). Result: The phytochemical screening results showed that the extract contained all tested compound groups. The antibacterial test against E. coli demonstrated significant activity starting from 60% (inhibition zone diameter of 10,70 ± 0,31 mm) to 80% (10,93 ± 0,35 mm) with no statistically significant difference (p > 0.05). Conversely, inhibition against P. aeruginosa was only observed at the highest concentration of 80% with an average diameter of 10,28 ± 0,23 mm. The extract concentration had a significant effect on the inhibition zone diameter (p < 0.0001). It can be concluded that the presence of flavonoids, tannins, and phenolics contributed to the antibacterial activity of the fresh Katuk leaf extract, highlighting its potential to be developed as a natural antibiotic and food preservative.